Transcatheter Closure of Ventricular Septal Rupture First in Bangladesh - A Case Report (Cardiovascular Journal, 2015)
Ventricular septal rupture is a rare complication of acute myocardial infarction with important hemodynamic consequences. Without a rapid diagnosis and correction by surgical intervention, the short-term mortality of these patients is higher than 90%. Early diagnosis is based on clinical examination and transthoracic echocardiography. Transcatheter closure of ventricular septal rupture in selected patients may save lives. We report a patient with ventricular septal rupture in acute myocardial infarction that was closed by an Amplatzer device. DOI: http://dx.doi.org/10.3329/cardio.v7i2.22264 Cardiovasc. j. 2015; 7(2): 150-152